Case Report: Functional characterization of a missense variant in INSR associated with hypoketotic hypoglycemia - Guzman, Herodes; Mitteer, Lauren M.; Chen, Pan; Juliana, Christine A.; Boodhansingh, Kara; Lord, Katherine; Ganguly, Arupa; De Leon, Diva D. (Frontiers in Pediatrics, 2024)
Hypoketotic hypoglycemia due to dysregulated insulin secretion is the most common cause of persistent hypoglycemia in children. However, this type of hypoglycemia can also result from defects in the insulin signaling pathway. Distinguishing between the two is important for informing treatment decisions. Here we describe the case of a 10-year-old female with fasting and postprandial hypoglycemia who was found to have a missense variant in the INSR gene, which we functionally characterized. The proband presented with fasting and postprandial hypoglycemia at age six. Diagnostic evaluation was consistent with hypoketotic hypoglycemia suspected to be due to hyperinsulinism, and she was treated with diazoxide. Whole exome sequencing identified a maternally inherited heterozygous missense variant in INSR. Phenotypic studies on the mother were consistent with postprandial hypoglycemia. Phosphorylated Akt and ERK1/2 levels were higher at baseline and in response to stimulation with insulin in 3T3-L1 cells expressing mutant INSR compared to cells expressing wild type INSR. Thus, herein we present a heterozygous missense variant in INSR (c.1151A>G, p.Asn384Ser) that results in constitutive and increased activation of the human insulin receptor, leading to both fasting and postprandial hypoglycemia.